Marketing and dentistry associated with ethical and legal knowledge on social networks by dentists (Research, Society and Development, 2023)
Social media marketing includes the promotion of ethical dental principles regarding oral health and disease prevention in patients. When associated with dentistry by dentists, it must be carried out in accordance with the standards of ethics recommended for the category, which function to regulate these activities. Thus, the research aimed to analyze the marketing associated with dentistry and in social networks by dentists. Methodology: descriptive literature review with a qualitative approach carried out from September to November 2022. The following databases were used: Portal de Periódicos da CAPES, SCIELO (Scientific Electronic Library Online) and BVS (Virtual Health Library), guided by the following keywords: “Marketing and Dentistry”, “Dental Ethics” and “Forensic Dentistry”. Results: The dental surgeon has great knowledge about the code of ethics in his work. But lacking specific knowledge about the use of marketing in social networks respecting all the points established by the regulation. Discussion: The perceptions, knowledge and practices related to marketing used by dentists were investigated from a different perspective, in which it was noted how important it is for professionals to promote their activities. Professionals seek training in the areas of marketing and advertising in an attempt to succeed in relation to their own demands, lacking a complete understanding of the importance of associating marketing with the ethics involved in these processes. Conclusion: there is no clear respect, on the part of professional dentists, in relation to resolution CFO-196/2019 when professional disclosure and advertising on social networks.